Analysis of the variables that contribute to self-organization for the management of family lands in the Yánesha Native Community Santa Rosa de Chuchurras, Pasco, Peru - Rios Pumayali, Yomira Fresia (2023)
This research analyzed the variables that contribute to self-organization within the general framework for analysing the sustainability of socioecological systems (SES). In our case study, a correlation analysis showed that 80% of the variables contribute to the self-organization of the community in relation to the key resource: family land. There was evidence of land use transition, initially dependent on agrosilvopastoral system, towards diverse economic activities and with it also the inclusion of informal norms (institutional bricolage). These changes stem from two circumstances that threaten community organization. The first is linked to the absence of legal recognition of family lands by the Peruvian State, despite the prioritization of family economic activities over collective actions. The second is the precarious road connectivity that makes exporting difficult, slowing down production and the quality of their supply. If these two circumstances were addressed through public policies: a) the emigration of the community's younger population would be reduced; b) foreign investment would be attractive in this community; c) would increase the flow of energy and information between the community and its environment improving social capital and trust; and finally, d) uncertainty would be reduced, strengthening community self-organization.